Effects of Parenting Programs on Reducing Parent Stress with Autism - Fitriasari, Andikawati; Yusuf, Ah; Kholidah, Nurilla (Universitas Airlangga, 2019)
Introduction: Parenting is very influential in the growth and development of children, especially if the child has autism. Generally, parents who have autistic children experience stress, therefore how the parenting program is very important to be studied so that parents can treat autistic children in achieving optimal development. This Systematic review aims to explain the effect of parenting programs in reducing the stress of parents with autistic children.Method: The journal search was conducted on the Scopus and Science Direct databases, journal restrictions in the last ten years starting 2008-2017, the journal areas of Nursing, Psychology, Disability, Child, and Psychiatry with the keywords Parenting, Parent Stress and Autism. Data selection and extraction procedures use the PICOT approach.Results: The total number of participants from all studies reviewed was 2107, with parents experiencing anxiety or stress due to having an autistic child. The interventions used in all research were parenting program interventions and parenting support. The average duration of intervention was three weeks with a mean follow-up of 12 months. Significant effects were found statistically from parenting programs or parenting support for outcomes post-intervention until follow-up. Significant results were found in parenting programs through researchers' counseling media accompanied by certified therapists.Conclusion: Parenting has a significant effect on reducing stress in parents who have autistic children.